GINGER AS AN ANIMAL FEED ADDITIVE: AN OVERVIEW - Rahmad Syukur Siregar; Yuli Widiyastuti; Muhammad Said Siregar; Marina Silalahi (Journal of Animal and Plant Sciences, 2024)
Ginger is a natural alternative to antibiotics and is safe for animal and human health. Its use has been reported as an animal feed additive without triggering antibiotic resistance or residues in products. Ginger contains a number of active compounds, viz., terpenes, oleoresin, zingiberol, zingiberone, zingiberene, gingerol, shogaol, zingerone, and paradol, which function as antioxidants, natural antibiotics, and immune stimulants to support animal health and growth. This article employed the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) method by identifying articles from various scientific report source databases, viz., PubMed, Scopus, Science Direct, and Elsevier. The articles and reports (n=130) were selected between the years 2014 to 2021. The literature survey findings revealed that ginger is a natural alternative to antibiotics that can increase the growth and productive efficiency of poultry, ruminant, and aquaculture. The use of ginger as a feed additive can support organic farming activities to protect the environment, humans, and animals, thereby potentially increasing the sustainability of the animal production sector.
Keywords: Aquaculture; ginger; phytogenic feed additives (PFA); poultry; ruminants; Zingiber officinale Roscoe